2022
DOI: 10.1002/pd.6202
|View full text |Cite
|
Sign up to set email alerts
|

Circulating trophoblast numbers as a potential marker for pregnancy complications

Abstract: Objective To explore the potential of circulating trophoblasts (TBs) as a non‐invasive tool to assess placental health and predict obstetric complications. Methods We retrospectively reviewed maternal characteristics and pregnancy outcomes of 369 women who enrolled in our original cell‐based NIPT (cbNIPT) study. The number of circulating TBs recovered from the maternal blood samples was recorded and expressed as fetal cell concentration (FCC). We evaluated if FCC can be used to predict pregnancy outcomes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…36 In a recent retrospective analysis of cbNIPT samples in our institution, we found that higher numbers of recovered TB were associated with hypertensive disorders of pregnancy. 30 These results are promising and open the way for other studies to investigate the potential of cbNIPT as a screening tool for medical conditions related to placental health. 30…”
Section: Other Applications Of Cbniptmentioning
confidence: 85%
See 3 more Smart Citations
“…36 In a recent retrospective analysis of cbNIPT samples in our institution, we found that higher numbers of recovered TB were associated with hypertensive disorders of pregnancy. 30 These results are promising and open the way for other studies to investigate the potential of cbNIPT as a screening tool for medical conditions related to placental health. 30…”
Section: Other Applications Of Cbniptmentioning
confidence: 85%
“…30 These results are promising and open the way for other studies to investigate the potential of cbNIPT as a screening tool for medical conditions related to placental health. 30…”
Section: Other Applications Of Cbniptmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, NIPS false-positive and false-negative test results have been highlighted by the US FDA in a recent safety communication [ 29 ]. There have been several recent studies demonstrating successful cell-based NIPD using trophoblasts from maternal blood [ 30 , 31 , 32 , 33 ] or from the cervix [ 34 , 35 , 36 ], which are present in the circulation at higher numbers, are easier to isolate, and are free of maternal DNA contamination; however, these studies do not totally avoid CPM [ 30 , 31 ]. Our results serve to highlight the advantage of FNRBCs over trophoblasts, namely, that FNRBCs represent the true fetal genotype, originating from the yolk sac and then from fetal liver at later gestations [ 37 ], and can be found within first-trimester placental villi, where they undergo terminal maturation processes [ 38 ], whereas trophoblasts are derived from the placenta.…”
Section: Discussionmentioning
confidence: 99%